Pop-Up Legenda Sindoro Sumbing Berbasis Kearifan Lokal sebagai Media Literasi Siswa - Ayu Wulandari; Theresia Pinaka Ratna Ning Hapsari (TRANSFORMATIKA, 2018)
This study aims to describe the steps of developing Sindoro Sumbing Legend pop-up media based on local wisdom as a student literacy media. This type of research is development research (R & D). This research was conducted at SDN Nguwet Kranggan, Temanggung Regency, Central Java, with a research subject of 35 class V students. The research instrument used in this study was a questionnaire. Questionnaires were filled in directly by respondents and validated by experts. The respondents who filled out the survey were teaching material experts, learning tool experts, and students. Data analysis techniques in this study used descriptive analysis. The results of this study are that Media Pop-Up developed is a Pop-Up folk tale or legend by linking local story elements in Temanggung Regency. This is due to the developed Pop-Up Book media based on local wisdom so that relevant stories are chosen, namely the Sindoro Sumbing Legend. Pop-Up Media Legend of Sindoro Sumbing based on domestic intelligence was developed with stages (1) research and data collection, (2) product manufacturing planning, (3) product draft development, and (4) limited implementation test. The results of the implementation tests in schools include individual tests, limited, and extensive tests obtaining scores in a row 4.25; 4.48; and 4.77, which means that the Pop-Up Legenda Sindoro Sumbing media is worthy of being used as a media for student literacy.